Implant retained mucous supported overdentures – a case report - Valentine Rosadi Sinaga; Setyawan Bonifacius; Rasmi Rikmasari (Indonesian Journal of Prosthodontic, 2023)
Background : The increase of life expectancy occurred along the demand of a denture that provides high masticatory efficiency to promotes high quality of life among the elders. Implant supported overdentures has been an attractive procedures because of its simplicity and minimal invasive, in which both the attachment part and mucous provide support, retention and stability. Objective : The purpose of this article is to show how to implement an implant and mucous supported overdenture with CBCT guidance to improve parallelized implant placement. Case report : a 55 years old female came referred to UNPAD Dental Hospital with complete loss of teeth. First phase of treatment was to make complete denture, following by duplicating the denture and used it as guidance in CBCT. Second phase was the implant stage which is two stage surgery. First stage surgery aimed to put two paralleled implant and followed by second stage surgery after three months. Conclusion : Implant overdentures has many advantages to elder patient, which is less invasive, simple reconstruction, provides facial support, retention, stability and easily removed for hygiene.